Strategies for the Use and Evaluation of Arabic Language Learning Media Based on the ASSURE Model - Sholihah, Umi Badriatus; Zuhri, Muh. Saifuddin (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This research is a qualitative study, with data collection techniques include documentation, interviews, and observation. The instructional development model used is the ASSURE model, which recommends six main activities in instructional planning: (A) Analyze the general characteristics of the target group.(S) State or formulate the learning objectives. (S) Select, modify, or design and develop appropriate materials and media. (U) Utilize the materials and media. (R) Require learner participation or responses. (E) Evaluate the learning process. There are various types of learning evaluation, including formative and summative evaluation. Formative evaluation is the process of collecting data during the development of instructional media with the aim of determining its feasibility. This evaluation includes several instruments that serve as parameters for assessing the quality of the media from the perspectives of content, educational value, and technical quality. Summative evaluation, is used to determine the effectiveness of the instructional media after its implementation. This includes written tests, performance assessments and practicum, portfolio assessments, project evaluations, and rubric-based assessments.